Implementing the Circular Economy for Sustainable Development, by Hans Wiesmeth, Amsterdam, Netherlands: Elsevier, 2020. 318 pp., $105. ISBN: 9780128217986 - Rahmatika, Maula Fadhilata (Global Economic, Social, and Development Review, 2025)
Book Review: Implementing the Circular Economy for Sustainable Development, by Hans Wiesmeth, Amsterdam, Netherlands: Elsevier, 2020. 318 pp., $105. ISBN: 9780128217986